2021
DOI: 10.4491/ksee.2021.43.10.664
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis and Review of Event Mean Concentrations in Stormwater Runoff from Agricultural Nonpoint Source Pollution among Different Land Use Types

Abstract: Objectives : In this study, the characteristics of stormwater runoff from agricultural nonpoint pollution sources investigated under various experimental conditions were evaluated among different land use types (e.g., paddy, field, field (alpine), and vinyl house), and event mean concentrations (EMCs) for each water quality parameter were statistically analyzed. These results can be used in calculating the contribution of stormwater runoff to water quality of receiving water body by performing quantitative and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…For the application of these techniques, BMPs are defined as the most appropriate methods to reduce the major NPSs discharged based on the characteristics of drainage areas during rainfall and improve water quality in Korea [14]. Therefore, appropriate BMPs were selected (draft), considering regional and environmental factors [15] as well as land use in drainage areas and maintenance by pollutants as in the following Table 4. In this study, among the structural methods that can quantify the NPS improvement effect [16,17], an artificial wetland with the highest removal efficiency for nutrients from soil and fertilizers [18] was selected considering the land use concentrated on agriculture and livestock housing [19].…”
Section: Methods Of Selecting Appropriate Bmpsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the application of these techniques, BMPs are defined as the most appropriate methods to reduce the major NPSs discharged based on the characteristics of drainage areas during rainfall and improve water quality in Korea [14]. Therefore, appropriate BMPs were selected (draft), considering regional and environmental factors [15] as well as land use in drainage areas and maintenance by pollutants as in the following Table 4. In this study, among the structural methods that can quantify the NPS improvement effect [16,17], an artificial wetland with the highest removal efficiency for nutrients from soil and fertilizers [18] was selected considering the land use concentrated on agriculture and livestock housing [19].…”
Section: Methods Of Selecting Appropriate Bmpsmentioning
confidence: 99%
“…The proportion of the area used for farming was as high as 99.8% for the Mulhan Stream and 99.9% for the Osan Stream. Studies that evaluated the major impact of NPSs that occur in rural areas [15,28,29] reported that the occurrence of NPSs increases during rainfall with the size of farmland. As in previous studies, the proportion of the area used for farming was also found to be high in the Mulhan Stream and Osan Stream with high BOD and TP pollution loads.…”
Section: Calculation Of the Nps Pollution Load By Subbasin Using The ...mentioning
confidence: 99%